Organizational Conflict: Concept and Dimensions - Amira Khaiat; Mohammed Lamine Slimane Tichtich; Said Ramdane (Ukrainian Policymaker)
his article analyzes organizational conflict by examining its definitions and identifying key causes, such as goal divergence, resource scarcity, and conflicting interests within organizations. The article classifies organizational conflict into three main dimensions: task conflict, process conflict, and interpersonal conflict. Task conflict involves differing views and perspectives on objectives and strategies, while process conflict focuses on disputes related to task execution and resource allocation. Interpersonal conflict refers to personal disputes and challenges between individuals.The study explores the relationships among these three dimensions by analyzing four previous studies conducted in various countries and sectors. It highlights the differences in correlation coefficients between dimensions, which vary depending on the organizational context and whether the sector is industrial or administrative. The findings suggest that the association between task conflict and process conflict differs across sectors, with a weaker correlation observed in the industrial sector due to the distinct separation of responsibilities between management and workers. In contrast, higher correlation coefficients were found in administrative and service sectors due to shared tasks and frequent interaction among personnel. The impact of process conflict on interpersonal conflict and the effect of interpersonal conflict on task conflict also varied depending on organizational culture and the degree of interdependence among individuals.The study adopts an operational definition of organizational conflict as a form of social interaction involving discrepancies among individuals regarding goals, work nature, approaches to execution, and solutions to challenges. It examines the impact of organizational conflict on the work environment and organizational performance, aiming to establish a comprehensive analytical framework for understanding and effectively managing organizational conflict to foster cooperation and achieve organizational goals.